Pengembangan E-modul Trainer Kontrol Motor Listrik dan PLC di Sekolah Menengah Kejuruan - Rahayu Kartin Ningsih; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This research discusses the development of e-module learning for Motor Control Trainer and PLC Trainer in the subject of Electrical Motor Installation Class XII TITL 1 at SMKN 1 Kec. Guguak. E-learning module is self-instructional which directs students to learn independently. Therefore, e-modules are a very good tool to use in the learning process and self-evaluate independently, thereby increasing learning outcomes. The purpose of this study is to develop a valid and practical e-module for learning. This type of research is research and development Research and Development. This research uses the 4-D model which consists of 4 steps, namely: define, design, develop, and disseminate. Collecting research data using validity and practicality questionnaires that have been validated by instrument expert lecturers. The results of e-module development research on the distribution of e-module validity questionnaires to respondents two Electrical Engineering lecturers and two Electric Motor Installation subject teachers got the average percentage results on very valid criteria. In distributing the e-module practicality questionnaire to respondents two teachers of the subject of Electric Motor Installation, they got the average percentage results on the very practical criteria and the e-module practicality questionnaire to the respondents 21 students got the average percentage results on very practical criteria. From the research data described, it shows that the development of e-modules made for the subject of Electrical Motor Installation has been criticized as valid and practical.